2011
DOI: 10.1002/chem.201003426
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Architecture of Discrete Organotin Sulfide Molecules by Optimization of the Intramolecular Spacer Length

Abstract: Measured approach: Organotin sulfide complexes adopt different structures depending on the length of the intramolecular organic spacer R, as shown by the synthesis of [(RxSn2)2(μ‐S)6] (e.g.; 1) or [Rx4Sn12S20] (2). For [(RxSn2)2(μ‐S)6], three different arrangements of the organic “straps” attached to [Sn4S6] cages are realized for different length ranges of Rx, whereas the longest spacer provokes a complete rearrangement of the inorganic core to form 2. DFT investigations rationalized the experimental findings. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…[9,10] It has been shown that it is possible to control the assembly of discrete organotin-sulfide moieties by the judicious selection of suitable bifunctional organic spacer groups. [11] However, investigations of the rearrangement of the inorganic core itself have not been implied so far, except for those on the unique formation of noradamantane-type structures [(RGe) 4 E 5 ]. [12] Herein, we report the synthesis and characterization of new organotin-chalcogenide complexes with the general formula [(R F Sn) 3 E 4 Cl] (E = S, Se).…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] It has been shown that it is possible to control the assembly of discrete organotin-sulfide moieties by the judicious selection of suitable bifunctional organic spacer groups. [11] However, investigations of the rearrangement of the inorganic core itself have not been implied so far, except for those on the unique formation of noradamantane-type structures [(RGe) 4 E 5 ]. [12] Herein, we report the synthesis and characterization of new organotin-chalcogenide complexes with the general formula [(R F Sn) 3 E 4 Cl] (E = S, Se).…”
Section: Introductionmentioning
confidence: 99%
“…In organotin sulfide chemistry, the formation of molecular capsules required larger spacer molecules to connect the two hydrazine groups of the parent cluster, with a maximum spacer length found with the 1,4‐bis(diazomethyl)benzene and 1,5‐bisnaphthalene‐functionalized groups, which led to the formation of macrocycles . However, in contrast to the reactions of organotin sulfide clusters, the cagelike compounds could not be obtained upon reaction of the “double‐decker”‐shaped [(R 2 Sn) 4 Se 6 ] precursor.…”
Section: Resultsmentioning
confidence: 92%
“…The structures of the cations in 3 – 5 also conform to the explanation for the ligand arrangement and structural rearrangement of the cluster core in terms of spacer lengths (C=N⋅⋅⋅N=C) . While the spacer length in 3 (4.33 Å) lies within the range for an anti ‐parallel arrangement of the ligands (4–6 Å), the spacer lengths in 4 a , 4 b , and 5 (9.44, 9.71, and 8.52 Å, respectively) are well above the lower limit for bigger capsules or cavitands (8 Å).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations